Paradigma Hakim dalam Menetapkan Tirkah dan Harta Bersama pada Keluarga Poligami: Analisis Putusan MA Nomor 107 PK/Ag/2016 - Abdul Kodir Alhamdani; Ahmad Firman (LEX FAMILIA: Journal of Islamic Family Law, 2026)
Inheritance disputes in polygamous families often present complex issues regarding the commingling of assets (vermenging) which are not rigidly accommodated by Article 94 of the Compilation of Islamic Law (KHI). This study aims to analyze the legal reasoning of Supreme Court Justices in determining the status of joint property (gono-gini) and inheritance estate (tirkah) in cases where physical assets are administratively controlled by a single wife. This research employs a qualitative method with a normative-juridical approach and a case study of the Judicial Review Decision Number 107 PK/Ag/2016. The findings indicate that the Supreme Court applied a progressive legal paradigm by introducing the concept of Collective Joint Property. The judges ruled that assets registered under the name of the third wife constitute joint property belonging to the marital union of the husband and all three wives collectively. Legally, the asset was separated (tashfiyah) into two equal parts: one half as the deceased's inheritance estate, and the other half distributed equally among the three wives as their joint property rights, regardless of marriage duration or certificate holdership. Furthermore, this study found that the judge's ex officio action to annul the Freehold Title Certificate (SHM) even though not explicitly requested in the lawsuit's petitum was not a violation of the ultra petitum partium principle, but rather an absolute juridical consequence to ensure legal certainty and the executability of the verdict. This study concludes that in polygamous inheritance disputes, judges tend to prioritize distributive justice and material truth over procedural formalities and administrative evidence.